Role of ATP-sensitive K(+)-channels in antiarrhythmic and cardioprotective action of adaptation to intermittent hypobaric hypoxia - Kolar, F; Nekar, J; Ostadal, B; Maslov, L N; Stakheev, D L; Tayurskaya, A S; Lishmanov, Yu B (Bulletin of experimental biology and medicine, 2008)
Mature Wistar rats were exposed to intermittent hypobaric hypoxia (5000 m, 6 h/day, 30 sessions). This mode of adaptation enhanced heart tolerance to the arrhythmogenic action of 45-min coronary occlusion, but does not affect the infarction size/risk area ratio. In some series, the rats were exposed to more severe intermittent hypobaric hypoxia (7000 m, 8 h/day, 6 weeks) followed by 20-min coronary occlusion and 3-h reperfusion one day after the last hypoxia session. In this case, adaptation reduced the infarction size/risk area ratio and enhanced cardiac tolerance to the arrhythmogenic effect of reperfusion, but had no effect on the incidence of ventricular arrhythmia during ischemia. We found that the cardioprotective and antiarrhythmic effects of adaptation to an altitude of 7000 m and the antiarrhythmic effect of 5000-m adaptation were mediated via activation of K(ATP) channels.
Keywords: Animals; thioamidy; ischemické přivykání; Hypoxia; Rats, Wistar; Altitude; fyziologická adaptace; Arrhythmias, Cardiac; nadmořská výška; hypoxie; Imidazoles; cytoprotekce; atmosférický tlak; Ischemic Preconditioning, Myocardial; srdeční arytmie; Adaptation, Physiological; Cytoprotection; krysa rodu Rattus; Thioamides; Atmospheric Pressure; zvířata; Myocardium; myokard; Rats; KATP Channels; KATP kanály; imidazoly; potkani Wistar